Heart–Hand Syndrome Type 1: A Case Report with Literature Review - Rashmi Nagaraj,; Kiran Hassan Srinivasa Murthy,; Sandeep Patil, (Indian Journal of Case Reports, 2021)
Holt-Oram syndrome (HOS) is the most common form of heart–hand syndromes and is inherited in an autosomal dominant fashion. It is characterized by the presence of upper limb and cardiac anomalies. A little more than 300 case reports have been published with various clinical features of HOS, even though the prevalence is as rare as 1 in 100,000 live births. We present here a young infant with not only upper limb and cardiac abnormalities, clinically diagnosed as HOS, but also with a minor lower limb anomaly. The related literature of clinical importance is also discussed.